Fermented Wheat Bran Polysaccharides Intervention Alters Rumen Bacterial Community and Promotes Rumen Development and Growth Performance in Lambs - Wang, Wenwen; Wang, Yuan; Cui, Zhiwei; Yang, Yi; An, Xiaoping; Qi, Jingwei (Frontiers in Veterinary Science, 2022)
There is a growing interest in the utilization of plant polysaccharides for the modulation of rumen bacterial community and enhancement of growth performance in ruminants. Fermented wheat bran polysaccharides (FWBPs), the plant polysaccharides, have been shown to improve growth performance of lambs, but little is know about their effect on rumen bacteria. The aim of this study was to investigate the effects of FWBPs supplementation to milk replacer (MR) on the growth performance, blood metabolites, weight and morphology of rumen, rumen fermentation, and rumen bacterial community were investigated in lambs. Twelve, 1.5-month-old crossbred lambs (Dorper × Small-tail Han Sheep) with an initial body weight (BW) of 11.38 ± 0.19 kg were randomly divided into two groups, including control group and FWBPs group. Compared with control group, FWBPs group had higher average daily weight gain and serum total protein concentrations, and lower feed: gain ratio. A tendency of increase in final BW and carcass BW were also observed. Administration of FWBPs increased ruminal papillae width and ruminal butyrate proportion, decreased concentration of ammonia nitrogen and the proportion of isobutyrate and isovalerate. In addition, the epithelial cell thickness had an increased trend in the FWBPs group. High-throughput sequencing data showed that the relative abundance of Lachnospiraceae_NK3A20_group and Solobacterium was enhanced by FWBPs treatment, meanwhile, the relative abundance of NK4A214_group, Megasphaera, and Treponema showed a tendency to be higher than the control group. Furthermore, Spearman’s correlation analysis revealed that the relative abundances of NK4A214_group, Treponema, and Lachnospiraceae_NK3A20_group were positively correlated with butyrate proportion. Collectively, FWBPs supplementation to MR on lambs altered rumen bacteria community, promoted rumen development and improved growth performance.